Retoryczny aspekt polemiki religijnej z perspektywy listu Stanisława Hozjusza do Marcina Kromera z 15 kwietnia 1551 roku - Stasiewicz, Przemysław (Studia Europaea Gnesnensia, 2016)
The aim of this paper is to show how a 16th-century Catholic clergyman would polemicize in the matter of religion with a Lutheran, whom he tried to convince to abandon erroneous (in his opinion) teachings. The author attempts to demonstrate the means and devices which Hozjusz employed for that purpose, and show the image of a heretic and a defender of faith conveyed in the letter to Marcin Kromer dated 15 of April 1551.